Flamingo foraging plasticity: ecological drivers and impacts - Gihwala, Kirti Narendra (Department of Biological Sciences, 2017)
The consequences of predation have become a central focus of marine ecological research. Numerous studies have emphasized the importance of apex predators in structuring assemblages at various organisational levels and in determining how ecosystems function. However, less appreciated currently is the fact that predators display multiple foraging behaviours, thereby allowing them to overcome problems associated with unpredictability of food resources in space and time. The primary goal of this dissertation is to contribute to growing understanding of the ecological causes and consequences of foraging plasticity displayed by Greater Flamingo Phoenicopterus ruber roseus in intertidal sandflat ecosystems in Langebaan Lagoon, South Africa. P. roseus feeds by either (1) creating pits, which involves flamingos stirring up deep sediments with their feet or (2) creating channels, in which their inverted bills are swept from side-to-side on the sediment surface. The first objective of the study was to quantify the ecological drivers of decisions made by flamingos to feed, and to implement either pit- or channel-foraging strategies. The latter was achieved through RandomForest modelling techniques that identified the prominent ecological drivers from a suite of biotic and abiotic variables. Results indicate that biotic variables, i.e. those associated with flamingo prey assemblages, were key in driving choices made by flamingos to forage and to implement either pit- or channel-foraging strategies. The second aim of this dissertation was to quantify the repercussions of the two different foraging behaviours on benthic assemblages. Comparisons of benthic assemblages in flamingo foraging structures (pits and channels) with adjacent non-foraged sediments (controls) indicated differential effects of both flamingo foraging methods on benthic communities, with channel-foraging eliciting a greater negative impact compared to pit-foraging, for which impacts were negligible. Abundance of macrofauna and surface-dwelling taxa such as micro-algae and the amphipod Urothoe grimaldii were all negatively impacted by channel-foraging. Sizes of channels constructed by flamingos were inversely related to their impacts, with impacts on macrofaunal abundance being greater in smaller channels. Overall, this study has shed light on the differential effects of foraging plasticity on prey assemblages and its importance in enhancing spatio-temporal heterogeneity in intertidal sandflats. The study also emphasizes the need to incorporate foraging plasticity into current thinking and conceptual models of predation in marine soft sediments, in order to appreciate the full spectrum of predation effects on assemblages.